Kontribusi Habits of Mind terhadap Efektivitas Strategi Pemecahan Masalah Matematika (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research investigates how habits of mind contribute to the success of students' mathematical problem-solving strategies. Using a quantitative method with a correlational survey approach, data were gathered from 76 junior high school students selected via purposive sampling. The instrument used was a questionnaire that focused on two aspects: students' habits of mind and mathematical problem-solving approaches. The analysis using simple linear regression revealed a notable correlation between habits of mind and students' problem-solving strategy effectiveness. The coefficient of determination (R²) was 0.719, indicating that 71.9% of the variation in effectiveness can be explained by habits of mind. These results emphasize the importance of integrating habits of mind into mathematics education to help students think more critically, reflectively, and systematically.